Substance Use in the Club Scene of Rome: A Pilot Study. (27th August 2014) - Vento, Alessandro Emiliano; Martinotti, Giovanni; Cinosi, Eduardo; Lupi, Matteo; Acciavatti, Tiziano; Carrus, Dario; Santacroce, Rita; Chillemi, Eleonora; Bonifaci, Ludovica; di Giannantonio, Massimo; Corazza, Ornella; Schifano, Fabrizio
Abstract : Objective . Over the last few years, a wide number of unregulated substances have been marketed on the Web and in smart and head shops; they are usually advertised as legal alternatives to commonly known drugs and are defined as "smart drugs, " "legal highs, " and "novel psychoactive substances" (NPS). Aim of our work is to describe use habits and distribution of NPS in a population of young adults in Rome club scene. Methods . A self-administered questionnaire was proposed to subjects over 18 years of age at the entrance of 5 nightclubs in Rome. Socioeconomic characteristics and substance use were investigated. Results . Preliminary results give evidence that 78% of respondents have a lifetime history of NPS use. In addition, 56% of the sample has consumed illicit drugs in the past and 39% has used psychoactive substances in the 12 hours preceding the questionnaire administration. Conclusions . A significant proportion of subjects report use of novel psychoactive substances; traditional illicit drugs consumption, particularly cocaine, appears to be very high as well in the club scene. These data highlight a serious public health challenge, since pharmacological, toxicological, and psychopathological effects linked to interactions among all these substances may be unpredictable and sometimes fatal in vulnerable individuals.